HOMBO BATU A TRADITIONAL ART THAT CAN BE EXPLAINED WITH THE LAWS OF PHYSICS - Harefa, Darmawan (Universitas Nias Raya, 2025)
This study aims to explain Hombo Batu, a traditional art from South Nias, using a physics approach to understand the physical principles involved in the game. The objective of this research is to identify physical concepts such as force, kinetic energy, and elasticity that influence the movement of the stones in the game. The method used is a literature review, in which the author examines relevant literature on Hombo Batu, basic physics, and theories related to the application of physics laws in traditional arts. The findings of the study show that Hombo Batu involves physical principles such as impact force, stone rebound, and energy transfer between the stones used. This research demonstrates that through an understanding of physics, the phenomena in Hombo Batu can be scientifically explained, offering a new perspective in connecting traditional culture with scientific knowledge.